Delaying Anticancer Drug Delivery by Self‐Assembly and Branching Effects of Minimalist Dendron–Drug Conjugates. Issue 41 (28th June 2018) - Correard, Florian; Roy, Myriam; Terrasson, Vincent; Braguer, Diane; Estève, Marie‐Anne; Gingras, Marc
Abstract: Self‐assembly of a covalently‐bound lipophilic drug to a dendronic scaffold for making organic nanoparticles is reported as a proof of concept in nanovectorization. A minimalist structural approach with a small PEG‐dendron conjugated to paclitaxel (PTX), incorporating safe succinic and gallic acids, is efficient to provide the expected anticancer bioactivity, but also significantly retards and targets intracellular delivery of PTX in 2D and 3D lung cancer cell cultures. A branching effect of dendrons is crucial, when compared to linear PTX conjugates. Transmission electron microscopy (TEM) and dynamic light‐scattering (DLS) studies indicate the formation of stable, low‐disperse nanoparticles at 10 −5 m in H2 0, which could also be responsible for the biological effects. An ultrasensitive LC‐MS/MS method was used for the determination of intracellular PTX concentration over time, along with the survival rates of cancer cells. Similarly, cell survival assays were successfully correlated to a 3D cell culture with spheroids for mimicking tumors, when treated with PTX conjugates. Our work opens the way to a full evaluation program required for new chemical entities. Abstract : Self‐assembly of a covalently‐bound lipophilic drug to a dendron for making organic nanoparticles is reported as a minimalist concept in nanovectorization. A small dendron conjugated to paclitaxel (PTX) provide nanoparticles and branching effects. It significantly retards intracellular delivery of PTX in 2D and 3D cell cultures. TEM/DLS studies are conclusive for monodisperse NPs. Intracellular PTX was measured by LC‐MS/MS. PTX conjugates were efficient in 3D cell cultures which mimic tumors. It provides a better mean to evaluate the in vitro efficacy of PTX‐conjugates to kill tumors.